PENERJEMAHAN TEMA PADA TEKS HUKUM - Sriyono Sriyono (Sunan Kalijaga State Islamic University Yogyakarta, 2014)
In translation, theme should be understood as the starting point of information flow. Furthermore, information structure in a legal text affect the interpretation of the legal meaning that will result in how the theme in legal text can be translated well. This study aims at describing kinds of theme and its translation both in the source text (Indonesian) and in the target text (English). It employs a qualitative-descriptive approach. The source of data is the document of Memorandum of Understanding (MoU) between the Government of Gunung Kidul District and International Relief and Development (IRD) in Indonesia and English version. Based on the analysis, this study indicates that the appearance of topical themes is more dominant than the appearance of textual themes is. The shift in the target text is influenced by the appearance of multiple themes in the source text. Conjunction as the representation of textual theme in the source text is also found in the form of double conjunction and possibly translated into verb and zero translation in the target text. Besides, emphasizing is a matter that specifically supports how the theme should be translated. Knowing and deciding the theme will enable to emphasize the information structure needed in either the source text or the target text.